Dance In Ancient Greece: Exploring the Legacy of Ancient Greek Dance (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Dancing has traditionally been one of the mostancient forms of community entertainment and, indeed, has been truethroughout  the history of the Greekseven asit is today. References to dance in ancient Greece have come down to usthrough the writings of Homer, Lucian, Plato and Socrates as well as others.Dance scenes are also depicted on many ancient ceramics.